Trauma and Conformity Trauma and Conformity. Psychology in THE ACT OF KILLING and DAS RADIKAL BÖSE - Hessel Jan Zondag (Journal for Religion, Film and Media, 2018)
This article discusses the psychological aspects of two documentaries about violence: THE ACT OF KILLING by Joshua Oppenheimer and DAS RADIKAL BÖSE (THE RADICAL EVIL) by Stefan Ruzowitzky. These are the concepts 'Trauma' and 'Conformism'. Both perspectives expose, provide insight and structure. But to both concepts question marks can be placed, because both of them also hide important elements of the violence described in the documentaries.